Limit theorems on lag increments of a Gaussian process - El-Shehawy, Shaban (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
This paper aims to establish limit theorems on the lag increments of a centered Gaussian process on a probability space in a general form under consideration of some convenient different statements.